Proceedings of 2012 IEEE-EMBS International Conference on Biomedical and Health Informatics 2012
DOI: 10.1109/bhi.2012.6211511
|View full text |Cite
|
Sign up to set email alerts
|

Development of e-health network for in-home pregnancy surveillance based on artificial intelligence

Abstract: The goal of the project is a telemedicine network of smart in-home monitoring systems for outpatient pregnancy surveillance to ensure early detection of pregnancy complications and fetal pathologies, as well as ubiquitous information support of pregnancy care both antenatal and intrapartum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 3 publications
0
16
0
2
Order By: Relevance
“…The approximate Shannon entropy of the normalized power spectral density of a very-low-frequency fetal heart rhythm signal, the aposterior FHR entropy, was used for sonographic signal quality assurance. It was demonstrated that the aposterior FHR entropy is ideal for detecting signal loss [1].…”
Section: B a New Approach To Ultrasound Monitoring Of Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…The approximate Shannon entropy of the normalized power spectral density of a very-low-frequency fetal heart rhythm signal, the aposterior FHR entropy, was used for sonographic signal quality assurance. It was demonstrated that the aposterior FHR entropy is ideal for detecting signal loss [1].…”
Section: B a New Approach To Ultrasound Monitoring Of Pregnancymentioning
confidence: 99%
“…In 2012 the project team participated in the International Conference of the IEEE-EMBS on Biomedical Informatics (BHI 2012) presenting a paper on the principle of in-home pregnancy surveillance using personal smart monitors [1]. Experts have acknowledged the novelty of the approach: information technology for large-scale pervasive, ubiquitous pregnancy care using personal web monitors, artificial intelligence, and cloud computing.…”
Section: A Innovative Architecturementioning
confidence: 99%
“…The best results were obtained by Iraji et al [51] using the Portuguese database showing an accuracy of 99.5%. There have also been some attempts to translate this into clinical practice via the development of software such as Infant, PeriCALM [52,53], and Foetos [54] or the development of mobile/website applications [55,56] to provide additional support in the interpretation of CTG signals and therefore to improve the assessment of fetal status. However, there is no evidence on whether these systems really improve the prediction of fetal distress or acidemia compared to visual CTG interpretation alone, and reports about their clinical performance were not found.…”
Section: For Fetal Diagnosismentioning
confidence: 99%
“…Early diagnosis and prevention of antenatal diseases are on the agenda now. Large-scale fetal monitoring could help if it were more pervasive [2,3]. However, there is the lack of ehealth technologies enabling low-cost remote services for broad-scale management of pregnancy.…”
Section: Introductionmentioning
confidence: 97%